1994
DOI: 10.1111/j.1600-0536.1994.tb02019.x
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of skin irritation

Abstract: Irritant contact dermatitis (ICD) is a multifactorial disease, the onset and modulation of which depend on both endogenous and exogenous factors. Among the former, age, race, site, sex and history of dermatitis may all be important. Such variables can now readily be quantified by objective noninvasive techniques, such as measurement oftransepidermal water loss (TEWL). Moreover, effects of irritants on the epidermis are related to the particular chemical properties of each molecule, contributing further to clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 49 publications
(42 reference statements)
0
36
0
2
Order By: Relevance
“…Generally, two different pathways (either alone or in combination) are associated with surfactants which can commence and regulate the cutaneous toxicity. First, by damaging the barrier function of the stratum corneum and second, by straightforward effects of surfactant on cutaneous cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, two different pathways (either alone or in combination) are associated with surfactants which can commence and regulate the cutaneous toxicity. First, by damaging the barrier function of the stratum corneum and second, by straightforward effects of surfactant on cutaneous cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…86 Many investigators use the model compound SLS to study the skin irritation response in human volunteers, because of its high irritant potential. 88 This irritant, an anionic surfactant, is frequently used as a foaming agent in cosmetic products such as shampoos, soaps, face and body washes and toothpaste. 84 Several studies reported a large variability in the response to SLS between individuals.…”
Section: Variability In Response To Irritantsmentioning
confidence: 99%
“…The events occurring in primary skin irritation represent a complex series of chemical and physiologic changes (Bason et al, 1991). In general, it is accepted that two different pathogenetic pathways may be involved in the process of skin irritation, firstly via damage to the lipid barrier of the SC and secondly via the direct irritation effect on cells of the skin (Berardesca & Distante, 1994;Welss et al, 2004). The skin irritation of a penetration enhancer would be likely more reversible if it only interacts with the intercellular lipids of the SC without affecting keratinocytes or others cells in the epidermis and dermis (Zesch, 1983).…”
Section: Further Considerationmentioning
confidence: 99%